2021
DOI: 10.3390/antiox10111704
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic Analysis and In Vitro Biological Activity of Red Wine, Pomace and Grape Seeds Oil Derived from Vitis vinifera L. cv. Montepulciano d’Abruzzo

Abstract: Grape pomace is commonly considered a waste product of monovarietal red wine production. Methods: HPLC-DAD analysis was performed to determine the polyphenol and flavonoid contents of all the extracts obtained from Montepulciano d’Abruzzo red wine and grape skins whereas, GC-MS was applied to the determination of fatty acid composition in grape seeds oil. Biological characterization involves antioxidant and antimicrobial assays for all the extracts and seeds oil; Their ability to inhibit α-glucosidase, α-amyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(35 citation statements)
references
References 73 publications
0
35
0
Order By: Relevance
“…HPLC analysis confirmed the presence of potent phenolics and phenylethanoid glycoside (verbascoside). Bioactive compounds found in plants also play important role in pharmaceutics and food industry, where some secondary metabolites showed potential biological activities ( Nescatelli et al, 2017 ; Stefanucci et al, 2018 ; Uysal et al, 2019 ; Lekhak et al, 2021 ; Mollica et al, 2021 ; Patel and Ghane, 2021 ). Ranade et al (2016) concluded that among phenolics, GA and CA were found the most common and abundant in leaves and stem of B. prionitis .…”
Section: Discussionmentioning
confidence: 99%
“…HPLC analysis confirmed the presence of potent phenolics and phenylethanoid glycoside (verbascoside). Bioactive compounds found in plants also play important role in pharmaceutics and food industry, where some secondary metabolites showed potential biological activities ( Nescatelli et al, 2017 ; Stefanucci et al, 2018 ; Uysal et al, 2019 ; Lekhak et al, 2021 ; Mollica et al, 2021 ; Patel and Ghane, 2021 ). Ranade et al (2016) concluded that among phenolics, GA and CA were found the most common and abundant in leaves and stem of B. prionitis .…”
Section: Discussionmentioning
confidence: 99%
“…The latter drugs may include naturally occurring antioxidants with anti-inflammatory functions that have been demonstrated to inhibit LOX-1 expression and activity in vascular cells [ 37 ]. Food that is rich in polyphenols and flavonoids was shown to have strong antioxidant and anti-inflammatory activity [ 38 , 39 ]. Indeed, procyanidins were reported to significantly decrease oxidized LDL uptake in LOX-1 expressing cells in vitro by inhibiting the binding of the scavenger receptor to its modified LDL ligand.…”
Section: Discussionmentioning
confidence: 99%
“…The general compositions of some grape marc have also been described [ 11 , 12 ]. Grape marc contains components that inhibit the proliferation of Caco-2 and HT-29 cancer cells by triggering apoptosis, has strong free radical scavengers and may provide some level of protection against certain cancers [ 13 ]. The profiles of phenolic compounds, recovered from waste from various wineries, were dominated by gallic acid, catechin and epicatechin.…”
Section: Introductionmentioning
confidence: 99%